Decomposition of Avicennia marina (Forsk.) Vierh. Foliage under field and laboratory conditions in the backwaters of Karachi, Pakistan (Bangladesh Journal of Botany, 2015)
The fate of leaf litter decomposition of Avicennia marina (Forsk.) Vierh. was found higher under field aerobic condition (FAC) while the fate was lowest under laboratory anaerobic condition (LAAC). The time required for the loss of half of the initial day weight (t50) was 48, 55, 98 and 110 days for aerobic condition (AC), field micro-aerobic condition (MAC), laboratory aerobic condition (LAC) and LAAC, respectively. Total nitrogen content of the decomposing litter increased by contrast, total organic carbon decreased during decomposition. Consequently, carbon to nitrogen ratios declined with time during decomposition. Repeated measure design showed that weight loss, total nitrogen and total organic carbon vary significantly under all four conditions with respect to elapsed time (p < 0.001; WilksLambda = 0.02, 0.003, 0.02, respectively at p < 0.001). The study concludes that mangrove litter has an initial rapid phase of decomposition and the variable decay rates depend on the degree of exposure/submergence of litter in water, the pressure of detrivores, and the oxygen level in the given niche of mangrove forest. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22716 Bangladesh J. Bot. 44(1): 1-7, 2015 (March)